Efficient recycling of trapped energies for dual-emission in Mn-doped perovskite nanocrystals - Wei, Qi (2020)
Doping impurity into semiconductor nanocrystals (NCs) is able to create novel optical, electronic, and magnetic functionalities. Recently, dual-emissions from Mn-doped lead chloride perovskites NCs have attracted much attention. However, the mechanisms of doping and energy-transfer to Mn ions of the perovskite NCs are still unclear. In this work, through the newly-developed post-treatment methods, it is found that excess Cl- can boost the Mn-emission due to the efficient ion diffusion and exchanges during Mn-doping processes. Importantly, a clear slow energy accumulation in the Mn dopants with time constant of ~ 200 ns is revealed from time-resolved photoluminescence (PL) measurements. Together with the doping insensitive band edge PL, these results indicate that the Mn dopants should snatch the energy from non-radiative trap states rather than from band states, which implies an efficient recycling of trapped nonradiative energy for luminescence by the dopants. The developed efficient doping method and proposed mechanism of energy transfer would provide unique insights into the mechanisms of doping. Moreover, fundamental investigations on nanostructure and optical properties are expected to increase its potential in electronic or magnetic applications.